Penta-1,2,3,4,6-O-Galloyl-β-d-Glucose Inhibits UVB-Induced Photoaging by Targeting PAK1 and JNK1 - Ji-An Kim; Jae-Eun Lee; Ji Hye Kim; Hyo-Jeong Lee; Nam Joo Kang (MDPI AG, 2019)
Penta-O-galloyl-β-d-glucose (PGG) is a gallotannin polyphenolic compound that occurs naturally in fermented Rhus verniciflua. The present study aimed to examine the effect of PGG on UVB-induced skin aging and its molecular mechanisms in HaCaT human keratinocytes and SKH-1 hairless mice models. PGG suppressed UVB-induced matrix metalloproteinase-1 (MMP-1) expression in HaCaT cells by inhibiting phosphorylation of RAF/MEK/ERK, MKK3/6/p38, and c-Jun. UVB-induced ERK and p38 signaling pathways that induce the MMP-1 expression were mediated by PAK1 in HaCaT cells. PGG suppressed PAK1 and JNK1 kinase activities, and directly bound both PAK1 in an ATP-competitive manner and JNK1 in an ATP-noncompetitive manner. Consistently, PGG decreased UVB-induced wrinkle formation, epidermal thickness, type 1 collagen and MMP-13 expression in mouse skin. Overall, these results indicate that PGG exhibits anti-photoaging effects in vitro and in vivo by the suppression of PAK1 and JNK1 kinase activities, and may be useful for the prevention of skin aging.